The rol of bowel preparation in colorectal surgery - Briola, Magali; Carballo, Federico Héctor Enrique (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Background: Mechanical preparation of the colon has been an essential practice for colorectal surgery. During the 1930's it was popularized on the grounds that stool, due to its bacterial content, predisposed to surgical site infections and favored anastomotic dehiscence. To reduce the incidence of surgical site infections, the use of antibiotic prophylaxis associated with mechanical preparation has been recommended. After some years and experimental studies in animals, emergency surgeries without preparation and good results, its use was questioned, in fact, it was sought to avoid the discomfort and morbidity involved. With the advent of laparoscopic surgery, it was questioned again since it was believed that it was necessary to prepare the colon to be able to manipulate it, but later it was demonstrated that it was not necessary. The relevance of this paper is to illustrate the changes described in the last decades regarding colonic preparation and to update the reader on current recommendations. Despite the controversies over the years, the paradigm is continuously changing. Material and methods: A systematic review was carried out with a literature search in the following databases: Google Scholar, Cocharme Library, Espistemonikos and PubMed (MEDLINE). The MESH search terms used in the present study were colorectal surgery; Surgical preparation; anastomotic leakage; bowel preparation; antibiotic prophylaxis. The Boolean operators OR and AND were used. By selecting potential papers and important information to identify the best outcome in patients undergoing elective colorectal surgery, a total of 363 articles were identified, of which a total of 30 were potential articles for this review. Results. Nine articles were selected after application of the inclusion and exclusion criteria. A total of 14,015 patients were studied, 54.60% were men and 45.40% were women.  The patients were divided into different groups, those who received only mechanical preparation of the colon, those who received mechanical preparation combined with oral antibiotics, those who received only oral prophylaxis and those who did not receive prophylaxis. Of the total number of studies analyzed, a clear reduction in complications was observed in the patients who received combined treatment. Conclusion: The combination of mechanical colon preparation and oral antibiotics would be associated with a lower incidence of surgical site infections and anastomotic leakage compared to no mechanical preparation